Benign phyllodes tumor with hemorrhagic cyst in a 14-year-old girl: A case report - Yoneyama, Kimiyasu (Int J Surg Case Rep, 2020)
INTRODUCTION: The incidence of mammary phyllodes tumor is less than 0.3–0.5% of all breast tumors. Only a few pediatric cases have been reported. Here we report a benign phyllodes tumor that occurred in a 14-year-old girl. PRESENTATION OF CASE: A left breast mass with a bleeding cyst of about 9 cm was resected after the tumor had rapidly increased in size over the course of 2 months. Imaging examinations suggested an intracystic tumor. Histopathological examination, however, revealed a benign phyllodes tumor without cytomorphism or mitotic figures. The tumor was accompanied by partial bleeding, which was considered to be the cause of the rapid increase in size of the hemorrhagic cyst. The patient remains under observation, and local recurrence has not occurred as of 3 years after surgery. CONCLUSION: Due to the rarity of the condition in children and adolescents, an individualized, case-based approach is recommended.